BioCrystal: An Ambient Tool for Emotion and Communication - Roseway, Asta; Lutchyn, Yuliya; Johns, Paul; Mynatt, Elizabeth; Czerwinski, Mary (IJMHCI, 2015)
In this paper we present the BioCrystal – a biofeedback device that uses physiological data to evaluate user’s affective states in real-time and signals the states via an ambient display. We evaluated the BioCrystal during a 2-week, in situ multi-method study during which ten users collected over 115 hours of usable data. Users’ comments suggested high utility of such a biofeedback device for self-awareness, stress-management and interpersonal communication. Quantitative data confirmed that the BioCrystal met the criteria of an ambient display, and significantly improved users’ ability to control their stress. We discuss practical applications and suggest directions for future development.